Pengaruh Koneksi Politik, Transfer Pricing, dan Strategi Bisnis terhadap Agresivitas Pajak Dimoderasi dengan Sales Growth - Cholva Dian Susanti S.; Ayunita Ajengtiyas Saputri Mashuri; Ekawati jati Wibawaningsih (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2021)
This research use quantitative method to find out the influences of political connections, transfer pricing, and business strategies on tax aggressiveness moderated by sales growth. Tax aggressiveness are measured using the cash effective tax rate (CETR) as a proxy, while political connections, transfer pricing, and business strategies are measured using a variable dummy. Meanwhile, sales growth as a moderator is measured by the sales growth ratio. Researchers selected all companies listed on the Indonesia Stock Exchange (BEI) from 2017 to 2019 as population research. The sample data observed were 260 sample data obtained through non-probability sampling, namely the purposive sampling method. The regression analysis of the panel data hypothesis testing used in this study and processed using STATA 16. The test results obtained include, (1) political connections, transfer pricing, and business strategies simultaneously have a significant influences on tax aggressiveness (2) sales growth are unable to strengthen or weaken political connections, transfer pricing, and business strategies influences to tax aggressiveness.